Pénétrer la boîte noire du traducteur - Fougner Rydning, Antin (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
A combination of the two process-oriented approaches to studying profes-sional translation online: (i) verbal reporting, better known as TAP (think-aloud protocols), and (ii) Translog, a program used for logging keyboard activity, yields interesting data about what goes on in the translator ’s mind during a translation task. Assuming that our interpretation of metaphorical expressions depend upon conceptual metaphors, examples selected from the online data of two experienced professional Norwegian translators are used to show how the translation of metaphorical concepts are handled. Possible ways of using the above-mentioned online data qualitatively to test the hypothesis according to which translation is more than an interlinguistic comparison, requiring the mobilisation of cognitive complements in the reformulation phase, are also suggested.